Islamic preventive measures on premarital teen sex: a religious model - Ismail, Nik Ahmad Hisham; Ahmad Sudan, Salmi; Nik Abdul Rahman, Nik Suryani; Ssekamanya, Siraje Abdallah (SAVAP International, 2012)
Premarital sex behaviors among adolescents or adults are subjected to the echoes of religious rules. Any form of sex outside marriage including adultery, homesexuality, rape, child sex abuse, lesbianism, prostitution, infidelity, and etc, is a criminal offence and subsequently prohibited in Islam. The objective of this research is to examine the positive of Islam ob premarital behaviors. The significance of the research lies on the facts that it studies the Islamic preventive measures on premarital on teachers. It is illegal and forbidden in the shari'ah; the general will of God which is revealed for the betterment of all mankind and for the protection of the progeny, family institution and the health of the individual. The methodology adopted in this research is library based analytical and evaluative methods. The data of this research is colleeted from reliable sources including the Qur'an and the hadith of the Prophet as well as other authentic sources. After various studies on the subject we know know that there are a range of factors that lead to premarital sex. These factors constitute; psychological factors, physical and social environment, sex orientations during the period of adolescence and puberty, global trend and economic status.